The Effect Of Environmental, Social, And Governance (ESG) Risks On Firm Value With Financial Performance As An Intervening Variable - Wahyuni, Sri; Ismawati, Iis; Nofianti, Nana (Universitas Sultan Ageng Tirtayasa, 2025)
This research aims to determine the influence of Environmental, Social, and Governance (ESG) risk on firm value with financial performance as an intervening variable. The intervening variable used in this research is financial performance as measured by the Return on Assets (ROA) ratio. Independent variables in this research, ESG risk is measured by the ESG Risk Score. The dependent variable used in this research is value companies as measured by Tobin's Q. The population of this study is companies listed in the IDX ESG Leaders index. The sampling method used was purposive sampling, and 15 companies were selected that met the criteria as research samples. The analytical method used is SEM-PLS `with SmartPLS 3 software. The results of this study show that ESG risk has a positive effect on firm value. Research also shows that ESG risk has a positive and significant effect on financial performance, and financial performance has a positive and significant effect on firm value. So that financial performance in this research can be used as an intervening variable.